Seidel spectrum for splitting V-vertex join and S-vertex join of graphs - Ramane, Harishchandra S.; Patil, Daneshwari D. (Indonesian Combinatorial Society (InaCombS), 2025)
Splitting V-vertex join and S-vertex join of graphs are the graph structures obtained from splitting graph of a graph. Present work concentrates on the study of Seidel spectrum for the vertex join structures considered.